International prostate symptom score - IPSS - AUA as discriminat scale in 400 male patients with lower urinary tract symptoms (LUTS) - Rodrigues,Paulo (2004)
OBJECTIVE: This study analyzed the total symptom score, irritative and obstructive domains of IPSS questions regarding quality of life and the urodynamic diagnosis in 400 men with LUTS. MATERIALS AND METHODS: Four hundred consecutive male patients were prospectively enrolled after being submitted to full urodynamic evaluation and IPSS. Obstructed and non-obstructed patients were compared regarding the symptoms score and quality of life. Results were assessed through Wilcox, ANOVA and Student-t tests. RESULTS: 80.2% were diagnosed as urodynamically obstructed of which 42.4% presented detrusor instability in the filling phase. In obstructed patients there were no statistical difference concerning obstructive or irritative questions from IPSS (p = 0.50). It was not possible either to predict which patients presented detrusor instability based on the questionnaire (p = 0.65). Out of seventy-nine cases unobstructed (19.8%), 65.4% revealed detrusor instability. These cases could not be distinguished from all obstructed men based on the clinical questions measured by IPSS (p = 0.87). Obstructive and irritative questions did not present different indexes than obstructed cases (p = 0.63). Subjective quality of life index did not discriminate obstruction nor it could predict detrusor instability in both groups. CONCLUSION: Clinical symptoms and quality of life index measured by the IPSS as well as its obstructive and irritative domains do not have discriminating power to predict the presence of infravesical obstruction in males with LUTS, demanding objective tools to demonstrate obstruction.